Study of high-frequency impact extrusion bionic drilling technology for soft coal seams - Tian, Hongjie; Tian, Dongzhuang; Chen, Zaixu (Frontiers in Earth Science, 2025)
Soft coal seams represent a common geological feature in coal and gas outburst mines. They generate a substantial amount of coal debris during gas extraction drilling, which easily causes hole blockage and leads to drilling hazards such as pipe sticking, pipe jamming, and borehole collapse. This study draws inspiration from the burrowing and soil discharge mechanisms of earthworms and proposes a novel composite drilling process that combines “impact vibration + crawling extrusion” for soft coal seams to mitigate these risks and enhance drilling efficiency. Based on discrete element simulation, the effects of drill bit structure, coal seam pressure, and coal seam condition on drilling performance are investigated. The results show that the concave cone bionic bit exhibits the best cutting performance at a buried depth of 400–600 m, with a drilling speed approximately 18% higher than that of other bit structures. The coal seam pressure demonstrates a negative correlation with drilling speed, and the bit displacement at 600 m is 32% lower than that at 400 m. In addition, the drilling efficiency in loose coal seams is considerably higher than in cohesive coal seams, with a displacement difference of 0.025 m/cycle. This study confirms that the proposed high-frequency impact extrusion bionic drilling technology can effectively enhance drilling efficiency and safety in soft coal seams, providing a theoretical basis for the design and optimization of related drilling equipment.